Reciprocity - McCarty, E. A. (Statistical and Social Inquiry Society of Ireland, 1879)
The existing depression of trade is the severest perhaps on record, and certainly has dragged us through as harassing a length of time as any that ever afflicted commerce. The distress sounds the circumstances of every class: the affluent and the poor realise the bitterness of industrial ills?the wealthy capitalist in gigantic losses suffers, while the labourer appears in the guise and condition of pauper, and landlord and tenant sigh at the prospect of the gale day. Widely extended and varied in oppressiveness, depression has seized the nations with a rigour unexampled in former experience. And this, too, at a time when the resources of the world appeared and really were of a richness and a power never before within reach of man. The potent agents for the production of wealth were in every form growing still more powerful to enrich the peoples and to minister to man's material welfare. Yet at just such a brilliant point came the paralysis of trade with all its inevitable and crashing miseries.
Read before the Society, 24 June 1979
Keywords: Reciprocity; International trade; Protectionism; Macroeconomic policy; 314.15